Physiologically‐Based Pharmacokinetic Modeling for the Prediction of CYP2D6‐Mediated Gene–Drug–Drug Interactions. (3rd July 2019) - Storelli, Flavia; Desmeules, Jules; Daali, Youssef
Abstract : The aim of this work was to predict the extent of Cytochrome P450 2D6 (CYP2D6)‐mediated drug–drug interactions (DDIs) in different CYP2D6 genotypes using physiologically‐based pharmacokinetic (PBPK) modeling. Following the development of a new duloxetine model and optimization of a paroxetine model, the effect of genetic polymorphisms on CYP2D6‐mediated intrinsic clearances of dextromethorphan, duloxetine, and paroxetine was estimated from rich pharmacokinetic profiles in activity score (AS)1 and AS2 subjects. We obtained good predictions for the dextromethorphan–duloxetine interaction (Ratio of predicted over observed area under the curve (AUC) ratio ( R pred/obs ) 1.38–1.43). Similarly, the effect of genotype was well predicted, with an increase of area under the curve ratio of 28% in AS2 subjects when compared with AS1 (observed, 33%). Despite an approximately twofold underprediction of the dextromethorphan–paroxetine interaction, an R pred/obs of 0.71 was obtained for the effect of genotype on the area under the curve ratio. Therefore, PBPK modeling can be successfully used to predict gene–drug–drug interactions (GDDIs). Based on these promising results, a workflow is suggested for the generic evaluation of GDDIs and DDIs that can be applied in other situations.